Autonomic computing in cloud resource management in Industry 4.0 - Choudhury, Tanupriya; Dewangan, Bhupesh Kumar; Tomar, Ravi; Singh, Bhupesh Kumar; Toe, Teoh Teik; Nhu, Nguyen Gia (Switzerland Springer, 2021)
This book describes the next generation of industry—Industry 4.0—and how it holds the promise of increased flexibility in manufacturing, along with automation, better quality, and improved productivity. The authors discuss how it thus enables companies to cope with the challenges of producing increasingly individualized products with a short lead-time to market and higher quality. The authors posit that intelligent cloud services and resource sharing play an important role in Industry 4.0 anticipated Fourth Industrial Revolution. This book serves the different issues and challenges in cloud resource management CRM techniques with proper propped solution for IT organizations. The book features chapters based on the characteristics of autonomic computing with its applicability in CRM. Each chapter features the techniques and analysis of each mechanism to make better resource management in cloud. Describes self-adaptable framework to find the best optimization techniques automatically based on issues and platforms; Presents a self-optimized model to find the optimal resource from the resource pool; Includes applications to diagnose and heal the system failure, and protect from malicious attacks.
Electronic reproduction
Keywords: Autonomic computing; Cloud computing; Industry 4.0.; Electronic books